2014
DOI: 10.5032/jae.2014.03032
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Blogging Habits of Agricultural Leadership Students: Understanding Motivation, Use, and Self-efficacy

Abstract: Blogging is a form of social media and student engagement is at the center of blogging. The benefits of blogging include ease in making writing easier to share, encouraging students to write outside of the classroom, and supporting group collaboration. The findings suggest students are more passive in their blogging experiences, as the data found students generally read blogs more than they wrote blogs. The unified theory on the acceptance and use of technology and self-efficacy were used as the framework for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Also, learners perceived that blog is easy to use compared to Twitter and online forum. The result is consonant with the findings of a study conducted by Bumguardner et al (2014) on 70 Students at Texas A&M University aimed at investigating the students' motivations in using blogs for intensive writing courses. It showed that the students felt that learning to operate blogs was easy for them, and ease of use indicates that the results and findings of previous studies are like this study.…”
Section: Discussionsupporting
confidence: 81%
“…Also, learners perceived that blog is easy to use compared to Twitter and online forum. The result is consonant with the findings of a study conducted by Bumguardner et al (2014) on 70 Students at Texas A&M University aimed at investigating the students' motivations in using blogs for intensive writing courses. It showed that the students felt that learning to operate blogs was easy for them, and ease of use indicates that the results and findings of previous studies are like this study.…”
Section: Discussionsupporting
confidence: 81%
“…Lai, Lai, and Jordan (2009) ;Luo, Li, Zhang, and Shim (2010); T. Zhou, Lu, and Wang (2010); Bumguardner, Strong, Murphrey, and Dooley (2014); and Marchewka and Kostiwa (2014) concluded PE influences BI. This leads us to hypothesize the following: Hypothesis 1 (H1): PE about mobile banking service technology has a positive impact on user's intention to adopt it.…”
Section: Hypothesis Developmentmentioning
confidence: 95%
“…According to SCT, there are six things that affect behavior: reciprocal determinism, behavioral capability, observational learning, reinforcements, expectations, and self-efficacy (Bandura, 1986). A person's behavior that influences and is influenced through social and external environments is reciprocal determinism (Bumguardner et al, 2014). Behavioral capability is a person's actual ability to execute a behavior through acquired knowledge (Bandura, 1986).…”
Section: Theoretical and Conceptual Frameworkmentioning
confidence: 99%